On understanding the applicability of Mohr-Coulomb failure hypothesis for composite materials using UnitCells© - Balasubramani, Nimal Kumar; Sitnikova, Elena; Li, Shuguang (2016)
The applicability of Mohr-Coulomb (M-C) failure hypothesis for anisotropic composite materials is re-examined in this paper. Mohr-Coulomb failure theory has been widely referred to in the literature to study the failure of unidirectional (UD) fibre reinforced composites under transverse loading including the renowned Puck’s criteria. This has been partially validated based on the experimental correlations with the predictions made by the M-C criterion for a few set of test cases, which remains a debatable way of formulating composites failure criterion. It is brought to attention that Mohr utilised the concept of principal stresses in constructing principal circles and assumed that the outermost circle represents the critical state of failure. This hypothesis and its derivative “failure is dictated by the stresses acting on the fracture surface” have thus been used for formulating the criterion for isotropic materials that exhibit brittle fracture characteristics. However, the concept of principal stresses is not employable in the analysis of composites. Hence, the same hypothesis may not be applicable in studying composite materials. Also, the micromechanical aspects that lead to failure have not been taken into consideration in this hypothesis which can lead to incorrect predictions in the case of composite materials. The capability of an appropriately representative unit cell model in better understanding the micromechanical aspects and the implications of the hypothesis is studied by attempting micromechanical analysis of UD composites through UnitCells© tool. It is utilised to locate stress concentrations within the unit cell from which the likely angle of the fracture surface can be identified. It has also been shown that the stress concentrations could help locate the fracture angle for UD composite materials as a sufficient but not a necessary requirement due to the presence of non-linear behaviour before fracture. If one wishes to employ M-C failure hypothesis to formulate a failure criterion, the assumption that the failure is determined by the stresses exposed on fracture surface has to be made with caution.